Improvements on IP - IAPP: A fast IP handoff protocol for IEEE 802.11 wireless and mobile clients - Christos Bouras; Ioanna Sampraku; T Karoubalis (WINET Journal, Special Issue on Broadband Wireless Multimedia, Kluwer Academic Publishers, Vol. 13, No. 4, 2007)
One of the most critical issues in introducingWireless LAN (WLAN) real-time and delay sensitive applications, such asVoice over IP (VoIP), is guaranteeing IP service continuation during inter-subnet Basic Service Set (BSS) transitions. Even though WLANs offer very high channel bandwidth, they exhibit long network-layer handoff latency. This is a restraining factor for mobile clients using interactive multimedia applications such as VoIP or video streaming. In a previous work, we presented a novel fast and efficient IP mobility solution, called ?IP-IAPP?, which offers constant IP connectivity to the 802.11 mobile users and successfully preserves their ongoing sessions, even during subnet handoffs (fast recovery of active connections). It is an 802.11-dependent IP mobility solution, which accelerates the network reconfiguration phase after subnet handoffs and significantly reduces the IP handoff latency. It restores L3 connectivity almost simultaneously to the L2 connectivity after a subnet handoff, due to a zero-delay movement detection method. As a result, even the most demanding next generation WLAN applications such as Voice over WLAN (VoWLAN) suffer insignificant disruption. In this paper we present an improved version of the IP-IAPP mobility mechanism (new optimized protocol procedures). Certain extensions have also been incorporated to the initial proposal, for the provision of more advanced services: (a) secure inter-AP IP-IAPP communications, (b) zero patching on the clients s/w, and (c) support of clients which use a dynamic IP address. Performance measurements out of further and more complex testing verify that the proposed method outperforms other existing mobility solutions, and still introduces the lesser imperative amendments to the existing 802.11 wireless LAN framework.